“Town of all trades” in Shilka: creation of a comfortable environment - Kazakova, Valentina (project baikal, 2021)
The concept of development and improvement was worked out for the All-Russian Competition for the best projects for a comfortable urban environment in small towns and historic settlements. The article considers the characteristics and the development capacity of a small town as a basis for a complex project. The design process has many stages. It is important to involve businesses, communities, authorities, social groups and users of the area at each stage.
Keywords: Shilka; public space; participatory design; improvements; urban identity; complex development of urban areas; small towns and historic settlements